Sustained involuntary muscle activity in cerebral palsy and stroke: same symptom, diverse mechanisms. Issue 1 (25th November 2019) - Forman, Christian Riis; Svane, Christian; Kruuse, Christina; Gracies, Jean-Michel; Nielsen, Jens Bo; Lorentzen, Jakob
Abstract: Individuals with lesions of central motor pathways frequently suffer from sustained involuntary muscle activity. This symptom shares clinical characteristics with dystonia but is observable in individuals classified as spastic. The term spastic dystonia has been introduced, although the underlying mechanisms of involuntary activity are not clarified and vary between individuals depending on the disorder. This study aimed to investigate the nature and pathophysiology of sustained involuntary muscle activity in adults with cerebral palsy and stroke. Seventeen adults with cerebral palsy (Gross Motor Function Classification System I–V), 8 adults with chronic stroke and 14 control individuals participated in the study. All individuals with cerebral palsy or stroke showed increased resistance to passive movement with Modified Ashworth Scale >1. Two-minute surface EMG recordings were obtained from the biceps muscle during attempted rest in three positions of the elbow joint; a maximally flexed position, a 90-degree position and a maximally extended position. Cross-correlation analysis of sustained involuntary muscle activity from individuals with cerebral palsy and stroke, and recordings of voluntary isometric contractions from control individuals were performed to examine common synaptic drive. In total, 13 out of 17 individuals with cerebral palsy and all 8 individuals with stroke contained sustained involuntary muscle activity. In individuals with cerebral palsy, the level of muscle activity was not affected by the joint position. In individuals with stroke, the level of muscle activity significantly ( P < 0.05) increased from the flexed position to the 90 degree and extended position. Cumulant density function indicated significant short-term synchronization of motor unit activities in all recordings. All groups exhibited significant coherence in the alpha (6–15 Hz), beta (16–35 Hz) and early gamma band (36–60 Hz). The cerebral palsy group had lower alpha band coherence estimates, but higher gamma band coherence estimates compared with the stroke group. Individuals with increased resistance to passive movement due to cerebral palsy or stroke frequently suffer sustained involuntary muscle activity, which cannot exclusively be described by spasticity. The sustained involuntary muscle activity in both groups originated from a common synaptic input to the motor neuron pool, but the generating mechanisms could differ between groups. In cerebral palsy it seemed to originate more from central mechanisms, whereas peripheral mechanisms likely play a larger role in stroke. The sustained involuntary muscle activity should not be treated simply like the spinal stretch reflex mediated symptom of spasticity and should not either be treated identically in both groups. Abstract : We show that sustained involuntary muscle activity exists in individuals with central motor lesions, but is a complex condition separate from spastic exaggerated stretch reflexes and might originate from different mechanisms in stroke and cerebral palsy. Distinction between spasticity and sustained involuntary muscle activity is vital for guiding treatment. Graphical Abstract: